2021 Update of the International Council for Standardization in Haematology Recommendations for Laboratory Measurement of Direct Oral Anticoagulants - Douxfils, Jonathan; Adcock, Dorothy M.; Bates, Shannon M.; Favaloro, Emmanuel J.; Gouin-Thibault, Isabelle; Guillermo, Cecilia; Kawai, Yohko; Lindhoff-Last, Edelgard; Kitchen, Steve; Gosselin, Robert C. (Thrombosis and haemostasis, 2021)
Abstract In 2018, the International Council for Standardization in Haematology (ICSH) published a consensus document providing guidance for laboratories on measuring direct oral anticoagulants (DOACs). Since that publication, several significant changes related to DOACs have occurred, including the approval of a new DOAC by the Food and Drug Administration, betrixaban, and a specific DOAC reversal agent intended for use when the reversal of anticoagulation with apixaban or rivaroxaban is needed due to life-threatening or uncontrolled bleeding, andexanet alfa. In addition, this ICSH Working Party recognized areas where additional information was warranted, including patient population considerations and updates in point-of-care testing. The information in this manuscript supplements our previous ICSH DOAC laboratory guidance document. The recommendations provided are based on (1) information from peer-reviewed publications about laboratory measurement of DOACs, (2) contributing author's personal experience/expert opinion and (3) good laboratory practice.